Gamification in Energy Consumption: A Model for Consumers’ Energy Saving - Bahman Huseynli (International Journal of Energy Economics and Policy, 2024)
In this study, the possibility of saving energy with gamification designed applications was investigated, literature studies on this subject were examined and a gamification-based approach was followed for energy saving. From this point of view, the aim of the study is to propose a gamification-based model to make energy saving easier, fun, enjoyable and beneficial. This study is exploratory qualitative research using systematic literature review, synthesis and induction methods. Within the scope of the study, the literature was first examined. The literature review focused on learning gamification-based designs that encourage energy consumption reduction. After that, a new model was developed based on the general principles of gamification, the characteristics of consumer behavior and the energy consumption target, which is the main subject of the study. As a result of the study, a gamification-based model is proposed for household consumers to reduce their energy consumption and save energy. This gamification-based model includes making energy savings easier and more beneficial for consumers, as well as making it more fun and enjoyable. After that, the proposed model was analyzed based on the studies in the literature and finally the potential of the proposed framework was discussed.